Rancang Bangun Pengembangan Sistem Agribisnis Beras di Wilayah Kabupaten Penukal Abab Lematang Ilir (PALI) - Lufiana, Lufiana; Maryadi, Maryadi; Purbiyanti, Erni (Publikasi Penelitian Terapan dan Kebijakan, 2024)
Rice is the staple food that consumed by 90% of the Indonesian people. Rice producing countries are expected to be able to meet their country's rice needs. The purpose of this study to describe the potential of land for rice farming. Describe the trend of rice productivity development. Analyze the output and outcome of rice agribusiness development system, describe production and consumption trend are felt. Analyze the Farmer Exchange Rate of rice. Analyze the factors that influence farmers' rice production. Analyze the factors that influence farmers' rice consumption. Analyze the strategy of the Design and Construction of the Rice Agribusiness System Development in the PALI Regency area. The research method used accidental sampling with a total of 75 respondents. The data used in this study are primary and secondary data. The results of this study are he land to be used is first tested for soil, the next step is to carry out the design of potential suitability class. In the actual land suitability class, it is dominated by limiting factor of Production Temperature. Farmers' rice consumption is influenced by factors such as the number of family members, mother's age, mother's education level, rice price and income